THE CONTRIBUTION OF DIGITAL LITERACY AND FIELD WORK PRACTICE TO THE EMPLOYABILITY SKILLS OF VOCATIONAL HIGH SCHOOL STUDENTS - Indah Wiyanti; Tuwoso Tuwoso; Imam Alfianto (SOSIOEDUKASI, 2025)
This inquiry seeks to determine the influence of digital literacy and fieldwork engagement on the employability competencies of SMK students. The study is situated within the broader discourse on enhancing adaptive graduate skills essential for navigating the complexities of contemporary labor markets under Industry 4.0 and Society 5.0. Utilizing a quantitative explanatory design, the investigation draws upon a population of 120 Grade XII students from three state-run vocational schools in East Java participating in Field Work Practice (PKL) programs. Data collection was conducted using a Likert-scale instrument, and subsequent analysis employed multiple linear regression facilitated by SPSS. The analysis demonstrates a statistically significant positive influence of digital literacy on employability skills (p = 0.000 < 0.05). An analogous positive and significant effect is observed for fieldwork practice (p = 0.001 < 0.05). Simultaneously, these two variables contributed 51.4% to the variation in SMK students' employability skills. These findings confirm that strengthening digital literacy and optimizing the implementation of internships are effective strategies for improving the job readiness and competitiveness of vocational school graduates in the digital era.